Returning to the university during the pandemic: Perspectives of midwifery students from a public university - Rojas-Vega , Jennifer (2021)
Objective: To determine the perspectives of midwifery students regarding the return to the theoretical and practical university activities in the context of a pandemic. Materials and methods: A cross-sectional analytical study involving 115 second- to fifth-year midwifery students from a public university in Lima. The number of students who agreed to return to the theoretical and practical activities, the resources they had and their family situation were evaluated. Adjusted associations were estimated using Poisson regression. Results: Fifty-eight point two six percent (58.26 %) [95 % CI: 48.93 – 67.03 %] of the participants agreed to returnto virtual theoretical activities and 6.09 % [95 % CI: 2.89 – 12,34 %] to hospital practical activities. Only 66.09 % had access to the Internet, a mobile device and an adequate study environment at home. Those who did not agree to return to the hospital practical activities had a history of a pathological condition (p < 0.001) and lived with two or more people over 65 years of age (p < 0.001). The main medical conditions of the relatives over 65 years of age were hypertension (36.89 %), diabetes (19.04 %) and obesity (15.47 %). Conclusions: The number of midwifery students who agreed to return to the hospitals was low mainly because they had ahistory of a pathological condition and lived with relatives over 65 years of age. About half of the participants had digital resources that allowed them to access to remote learning.